2020
DOI: 10.1002/adfm.202000024
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Dual‐Channel Transition‐Metal‐Oxide Quasiaerogels by Self‐Embedded Templating

Abstract: The lack of precise control of particle sizes is the critical challenge in the assembly of 3D interconnected transition-metal oxide (TMO) for newlyemerging energy conversion devices. A self-embedded templating strategy for preparing the TMO@carbon quasiaerogels (TMO@C-QAs) is proposed. By mimicking an aerogel structure at a microscale, the TMO@C-QA successfully assembles size-controllable TMO nanoparticles into 3D interconnected structure with surface-enriched carbon species. The morphological evolutions of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…This performance was compared with those of recently reported oxide-based EWS systems (Figure 7d). [78,85,87,91,92,94,96,[102][103][104][105] The obtained results confirmed that CMO-U@CC exhibited improved electrocatalytic activity with faster kinetics and good stability.…”
Section: Aqueous Rechargeable Zinc-air Battery-driven Electrochemical Water Splittingsupporting
confidence: 64%
See 2 more Smart Citations
“…This performance was compared with those of recently reported oxide-based EWS systems (Figure 7d). [78,85,87,91,92,94,96,[102][103][104][105] The obtained results confirmed that CMO-U@CC exhibited improved electrocatalytic activity with faster kinetics and good stability.…”
Section: Aqueous Rechargeable Zinc-air Battery-driven Electrochemical Water Splittingsupporting
confidence: 64%
“…Figure 4f shows that the OER activity of the CMO-U@CC electrode was superior to those of many outstanding oxide-based electrocatalysts. [19,[40][41][42]45,48,49,[66][67][68][85][86][87] After testing the OER activity, CMO-U@CC was characterized via XPS, XRD, and FESEM analysis (Figure S8a-c, Supporting Information). The XPS characteristic peaks of Co 2p and Mn 2p shifted to higher oxidation states compared with those of CMO-U@CC before OER because of the surface oxidation.…”
Section: Oer Electrocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Aerogels are porous materials with nanostructures and exhibit promising potential for heat management due to their high porosity, low density, large specific surface area and low thermal conductivity [10][11][12][13][14]. In the past few decades, a variety of aerogel materials have been suc-cessfully prepared, including graphene [15][16][17], silica [18], carbon nanotubes [19,20] and synthetic polymers [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The microstructures of MS-(MMT/G) n were accurately controlled by tailoring the deposition numbers. Looking at the morphology of the pristine MS, a 3D open-cell scaffold structure within the MS (Figure b,c) accelerated the penetration of the aqueous dispersion through macropores during the assembly . With an increased assembly number of MMT/G layers, wrinkled structures on the surface gradually came up, while the open-pore structure was maintained (Figure d,f,h).…”
Section: Resultsmentioning
confidence: 98%